2016
DOI: 10.1371/journal.pone.0150113
|View full text |Cite
|
Sign up to set email alerts
|

Excessive Pro-Inflammatory Serum Cytokine Concentrations in Virulent Canine Babesiosis

Abstract: Babesia rossi infection causes a severe inflammatory response in the dog, which is the result of the balance between pro- and anti-inflammatory cytokine secretion. The aim of this study was to determine whether changes in cytokine concentrations were present in dogs with babesiosis and whether it was associated with disease outcome. Ninety-seven dogs naturally infected with B. rossi were studied and fifteen healthy dogs were included as controls. Diagnosis of babesiosis was confirmed by polymerase chain reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
102
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(109 citation statements)
references
References 64 publications
6
102
0
1
Order By: Relevance
“…Also, the monocyte chemoattractant protein (MCP-1) and the keratinocyte chemotactic-like protein were the cytokines found in the study which could discriminate complicated from uncomplicated cases [105]. Those results are consistent with previously reported data for canine babesiosis caused by B. rossi in which non-survivors showed an increased concentration of MCP-1, indicating that this protein could be a marker of poor outcome [88]. A study of Zygner et al [106] showed an increase of tumor necrosis factor alpha (TNF-α) serum concentration during canine babesiosis caused by B. canis.…”
Section: Systemic Infl Ammatory Response Syndromesupporting
confidence: 91%
See 1 more Smart Citation
“…Also, the monocyte chemoattractant protein (MCP-1) and the keratinocyte chemotactic-like protein were the cytokines found in the study which could discriminate complicated from uncomplicated cases [105]. Those results are consistent with previously reported data for canine babesiosis caused by B. rossi in which non-survivors showed an increased concentration of MCP-1, indicating that this protein could be a marker of poor outcome [88]. A study of Zygner et al [106] showed an increase of tumor necrosis factor alpha (TNF-α) serum concentration during canine babesiosis caused by B. canis.…”
Section: Systemic Infl Ammatory Response Syndromesupporting
confidence: 91%
“…The possible causes are formation of platelet-leukocyte aggregates, sequestration, increased utilisation and reduced production [88,89]. One possible mechanism involved in leukopenia includes the ability of platelets to interact with leukocytes and induce their so-called ˝secondary capture˝.…”
Section: Leucopenia and Thrombocytopeniamentioning
confidence: 99%
“…The observed concentration of each analyte for each sample was calculated using a standard curve generated from the seven standards and a blank provided by the manufacturer. For each cytokine, multiplex data recorded out of range were assigned the respective lowest or highest extrapolated values; samples were not diluted and retested because of cost restraints . The values were reported in pg/mL.…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that a proinflammatory state occurs in babesiosis that is associated with increased concentrations of markers of endothelial cell activation and altered hemostasis [6, 26]. Because canine babesiosis could be accompanied by endothelial dysfunction, the relationship between endothelial function and fibrinolytic balance needs to be examined in more detail.…”
Section: Introductionmentioning
confidence: 99%